Birlik kubdagi sodda differensial o’yinlarda quvish masalasi - Zunnunov, A.O; Esbosinov, R.E (SCIENCE and SOCIETY, 2019)
The article deals with the pursuit problem with simple motions in the sense of l-capture on a single cube in space. A structure is proposed for constructing piecewise constant persecution directorates which will ensure the completion of the game in a finite time. It was established a score above the time of the game to complete the pursuit.
Keywords: pursuit; pursuer; evader; pursuit control; evasion control